Factors Associated With Oral Cancer Adverse Outcome at the Rwanda Military Hospital, a Retrospective Cross-Sectional Study - Ndayisabye, Halifa; Ndagijimana, Albert; Biracyaza, Emmanuel; Umubyeyi, Aline (Frontiers in Oral Health, 2022)
Oral cancer (OC) is one of the most common cancers that remain global public health concerns in low-and middle-income countries. The epidemiology of OC in Africa endures uncertain. Earlier reports suggested a relatively low incidence of OC among Africans. Acting on behavioral factors and setting early diagnosis and treatments of OC can tremendously reduce morbidity and mortality related to it. This study determined factors associated with the OC adverse outcome and death in the Rwanda Military Hospital. A cross-sectional study was conducted among 311 medical records of patients who consulted in the Oral and Maxilla Facial Department between January 1st, 2007 and December 31st, 2019. Associated factors were estimated by use of odds ratios (OR) with their 95% confidence intervals (CI) in bivariate and multivariate logistic regression analyses to estimate predictors of OC adverse outcome and death. Almost three quarter of participants were from rural areas (n=229, 73.6%) and alcohol users (n=247, 79.1%). Concerning primary site infection, 54.02% of participants had the intra-oral cavity within the past 5 years. Muslims had greater odds to experience OC adverse outcome and death [aOR=6.7; 95% CI (3.8-11.9), p<0.001] than the Catholics. Those with no formal education was significantly had greater likelihoods to have OC adverse outcome and death [aOR=2.6;95% CI (1.3-5.3), p=0.005] than those with higher education or University. Those with primary education had greater likelihoods [aOR=1.8;95% CI (1.1-3.1), p=0.03] to have OC adverse outcome than those with higher or University education. Those with oral hygiene had less risk to have OC adverse outcome and death [aOR=0.2;95% CI (0.0-0.9), p=0.039] than their counterparts. Using multi-sectorial approaches including policy makers, clinicians and researchers from public and private institutions may be of an added value to promote clinical research on OC for earning knowledge contributing to combat risk behaviors and improve the population’s information and education on OC prevention.